From legacy effects of acid deposition in boreal streams to future environmental threats - Laudon, Hjalmar; Sponseller, Ryan A.; Bishop, Kevin (2021)
Few environmental issues have resulted in such a heated policy-science controversy in Sweden as the 1990s acidification debate in the north of the country. The belief that exceptionally high stream acidity levels during hydrological events was caused by anthropogenic deposition resulted in a governmentally funded, multi-million dollar surface-water liming program. This program was heavily criticized by a large part of the scientific community arguing that the acidity of northern streams was primarily caused by naturally occurring organic acids. Here, we revisit the acid deposition legacy in northern Sweden two decades after the culmination of the controversy by examining the long-term water chemistry trends in the Svartberget/Krycklan research catchment that became a nexus for the Swedish debate. In this reference stream, trends in acidic episodes do show a modest recovery that matches declines in acid deposition to pre-industrial levels, although stream acidity continues to be overwhelmingly driven by organic acidity. Yet there are legacies of acid deposition related to calcium losses from soils, which are more pronounced than anticipated. Finally, assessment of these trends are becoming increasingly complicated by new changes and threats to water resources that must be recognized to avoid unnecessary, expensive, and potentially counterproductive measures to adapt and mitigate human influences. Here we make the argument that while the acidification era is ending, climate change, land-use transitions, and long-range transport of other contaminants warrant close monitoring in the decades to come.